Digital asset ecosystems rethinking crowds and clouds - Blanke, Tobias (Chandos information professional series, 2014)
This book reflects on the state of digital asset management and what the emerging 'web of things' could mean for managing, using and publishing digital assets. It introduces the emerging ecosystems of digital assets, examines digital asset management in a networked environment, and covers media ecosystems.